Fe-phyllosilicate redox cycling organisms from a redox transition zone in Hanford 300 Area sediments - Benzine, Jason; Shelobolina, Evgenya; Xiong, Mai Yia; Kennedy, David W.; McKinley, James P.; Lin, Xueju; Roden, Eric (Frontiers in Microbiology, 2013)
Microorganisms capable of reducing or oxidizing structural iron (Fe) in Fe-bearing phyllosilicate minerals were enriched and isolated from a subsurface redox transition zone at the Hanford 300 Area site in eastern Washington, USA. Both conventional and in situ “i-chip” enrichment strategies were employed. One Fe(III)-reducing Geobacter (G. bremensis strain R1, Deltaproteobacteria) and six Fe(II) phyllosilicate-oxidizing isolates from the Alphaproteobacteria (Bradyrhizobium japonicum strains 22, is5, and in8p8), Betaproteobacteria (Cupriavidus necator strain A5-1, Dechloromonas agitata strain is5), and Actinobacteria (Nocardioides sp. strain in31) were recovered. The G. bremensis isolate grew by oxidizing acetate with the oxidized form of NAu-2 smectite as the electron acceptor. The Fe(II)-oxidizers grew by oxidation of chemically reduced smectite as the energy source with nitrate as the electron acceptor. The Bradyrhizobium isolates could also carry out aerobic oxidation of biotite. This is the first report of the recovery of a Fe(II)-oxidizing Nocardioides, and to date only one other Fe(II)-oxidizing Bradyrhizobium is known. The 16S rRNA gene sequences of the isolates were similar to ones found in clone libraries from Hanford 300 sediments and groundwater, suggesting that such organisms may be present and active in situ. Whole genome sequencing of the isolates is underway, the results of which will enable comparative genomic analysis of mechanisms of extracellular phyllosilicate Fe redox metabolism, and facilitate development of techniques to detect the presence and expression of genes associated with microbial phyllosilicate Fe redox cycling in sediments.